2012
DOI: 10.1186/1472-6963-12-44
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing, direct nursing care hours and patient mortality in Taiwan: the longitudinal analysis of hospital nurse staffing and patient outcome study

Abstract: BackgroundStudies over the past decades have shown an association between nurse staffing and patient outcomes, however, most of these studies were conducted in the West. Accordingly, the purpose of this study aimed to provide an overview of the research/evidence base which has clarified the relationship between nurse staffing and patient mortality of acute care hospital wards under a universal health insurance system and attempted to provide explanations for some of the phenomena that are unique in Taiwan.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
1
40
0
3
Order By: Relevance
“…Similarly, it has been found previously that balancing nursing work assignments significantly affects nurses' and patients' satisfaction (Acar & Butt, ; Liang, Chen, Lee, & Huang, ). Previous research indicated that insufficient nurse staffing was associated with increased medical errors, adverse medical outcomes and increased mortality (Liang et al, ). Previously Khademi, Mohammadi, and Vanaki (), in a qualitative study in Tehran similarly found that nurses mainly experience excessive workload by the high proportion of patients to nurses, shortage of necessary equipment, assigning tasks for nurses without previous preparation and assigning nurses to perform irrelevant non‐medical tasks.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similarly, it has been found previously that balancing nursing work assignments significantly affects nurses' and patients' satisfaction (Acar & Butt, ; Liang, Chen, Lee, & Huang, ). Previous research indicated that insufficient nurse staffing was associated with increased medical errors, adverse medical outcomes and increased mortality (Liang et al, ). Previously Khademi, Mohammadi, and Vanaki (), in a qualitative study in Tehran similarly found that nurses mainly experience excessive workload by the high proportion of patients to nurses, shortage of necessary equipment, assigning tasks for nurses without previous preparation and assigning nurses to perform irrelevant non‐medical tasks.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, it has been found previously that balancing nursing work assignments significantly affects nurses' and patients' satisfaction (Acar & Butt, 2016;Liang, Chen, Lee, & Huang, 2012). Previous research indicated that insufficient nurse staffing was associated with increased medical errors, adverse medical outcomes and increased mortality (Liang et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is likely in part because more than a third of all cases of non-adherence can be attributed to forgetfulness [21]. Since forgetting to take one’s medicines, sometimes referred to as “unintentional non-adherence,” seems to be reinforced by social and economic factors; the next two sections will examine how alignment of social and health system forces could help to overcome these lapses in memory [22]. …”
Section: Patient-related Factorsmentioning
confidence: 99%
“…The adequacy of nurse staffing is closely related to patient safety and care quality (Liang et al . ); nurses are an essential component of the health‐care delivery system and play an important role in patient‐centred care. Thus, hospitals should hire sufficient numbers of nursing staff to reduce the workload.…”
Section: Discussionmentioning
confidence: 99%